SETTLEMENT OF NON-PERFORMING LOAN THROUGH MEDIATION AT BANK OF CENTRAL ASIA CO., LTD. OF BENGKULU BRANCH OFFICE - Tara Maziyyah; Edytiawarman Edytiawarman; Widiya N Rosari (Bengkoelen Justice : Jurnal Ilmu Hukum, 2021)
This study aims to determine and analyze the settlement of problem loans through the mediation of PT. Bank Central Asia Bengkulu Branch and to identify and explain the obstacles that arise in the settlement of non-performing loans at PT. Bank Central Asia, Bengkulu Branch. The research method used is empirical legal research, the research location was at PT Bank Central Asia Bengkulu Branch Office, the data collection technique was carried out through interviews. In PT Bank Central Asia, Bengkulu Branch, there are 178 people who are debtors. If the debtor does not fulfill his obligations, there will be default, which can cause the credit activity to become a non-performing loan. The settlement of non-performing loans at PT Bank Central Asia, the bank first carries out the negotiation stage, if the obligations are still not fulfilled by the debtor, the next step is to carry out the mediation process. The process of settling non-performing loans through mediation at PT Bank Central Asia Bengkulu Branch is carried out by means of internal mediation, which is the mediator, namely from the Legal and Compliance Task Force team at the Sentul Head Office, Bogor. There are 7 debtors who have completed problem loans until the mediation stage. The non-performing loan settlement process has never been carried out by means of litigation and never through OJK. Inhibiting factors have 2 causes, namely from internal factors and external factors. The suggestion for this research is to provide insights about the mediation process to the debtor so that the debtor understands the mediation process.